The Association between Hand Grip Strength and Forearm Dimensions in Healthy Bangladeshi Female Tea Garden Workers - Hasan, Abul; Paul, Pankaj; Choudhury, Sudipta; Pathan, Md Azmal Khan; Yeasmin, Farhana; Das, Anamika (Bangladesh Journal of Medical Education, 2025)
Background: The evaluation of anthropometry is beneficial to different prospective research. Anthropometric study data also provides information on what kind of labor is performed by an individual. Hand grip strength can vary based on several factors, the primary one being the type of work that the person performs. In our country, the tea garden sector employs a large number of people. The purpose of this study was to evaluate the forearm anthropometry and grip strength of the female tea garden laborers of Bangladesh. Materials and methods: This was a cross-sectional descriptive type of study. The study was carried out at the Anatomy Department of Sylhet MAG Osmani Medical College in Sylhet. The total duration of the study was one year. A total of one hundred female tea state employees were enlisted for this study. The women tea garden workers, age ranging in age from 20 to 50 years, were specifically chosen. Data was collected by researchers themselves and documented in a pre-designed data sheet. The individuals' forearm length and carrying angle of both sides were measured. The grip strength of the dominant and non-dominant hands was also measured. The data were displayed as a percentage and mean ± SD. Regression analysis for the correlation was conducted. Tables and figures were used for data presentation. Results: The mean carrying angle were 13.39±1.21 and 13.09±1.07 cm on the right and left side respectively. The mean forearm length was 22.77±1.67 cm and 22.64±1.63 cm on the right and left side respectively. The mean right hand grip strength was 25.82±2.76 kg. The mean left hand grip strength was 17.74±1.82 kg. Significant positive relationship of hand grip strength was found with carrying angle and forearm length of both side. Conclusion: Forearm length and carrying angle were positively correlated with the dominant handgrip strength of female tea garden workers in Bangladesh. BJME, Volume-16, Issue-01, January 2025: 40-48